Technology of Molding Masses for Architectural and Artistic Ceramics Using Low-Aluminate Clays - Chopenko, Nina; Muravlev, Vladimir; Skorodumova, Olga (International Journal of Engineering and Technology, 2018)
The article deals with the main technological problems arising in the manufacture of large-scale ceramic products for architectural and artistic purposes. The influence of low-burned chamotte obtained from low-alumina clay on the physical and mechanical properties of molding masses based on the Oposhnya clays is investigated. It is shown that the firing medium of the developed molding masses significantly affects the properties of ceramic products.Â